Best proximity points for p-summing cyclic orbital Meir–Keeler contractions - Zlatanov, Boyan (Nonlinear Analysis: Modelling and Control, 2015)
We generalize the cyclic orbital Meir–Keeler contractions, which were introduced by S. Karpagam and S. Agrawal in the context of p-summing maps. We found sufficient conditions for these new type of maps, that ensure the existence and uniqueness of fixed points in complete metric spaces, when the distances between the sets are zero, and the existence and uniqueness of best proximity points in uniformly convex Banach spaces.